A phytoplankton growth assay for routine in situ environmental assessments - Moreira-Santos, Matilde
This study proposes an ecologically relevant and cost-effective phytoplankton growth assay for routine in situ toxicity assessments. Assay procedures were developed applying, to the extent possible, the rationale behind the design of standard algal assays. Chlorella vulgaris was selected as test species because it grows well immobilized in alginate beads and has a wide geographic distribution. The performance of the assay in a freshwater system impacted by acid mine drainage demonstrated the suitability of assay chambers and procedures. The test system, made of inexpensive materials, allowed the rapid and easy deployment of the assay. The deployment of extra chambers at reference sites provided the ability to periodically check whether algal growth had already reached recommended growth criteria (time at which the assay should end). By deploying chambers filled with control medium at all sites, temperature was identified to explain 95% of the variation in growth. By using an artificial nutrient source shown capable of promoting algal growth according to recommended standards toxicity from the mine effluent was distinguish from in situ nutrient limitation effects. The very good agreement (r(2) = 90%) between mean in situ growth rates estimated by microscopy and by spectrophotometry and their similar coefficient of variation showed the latter to be a suitable straightforward methodology for assay endpoint estimation.